Deletion of the Thrombin Proteolytic Site in Neurofascin 155 Causes Disruption of Nodal and Paranodal Organization - Dutta, Dipankar J.; Fields, R. Douglas (Frontiers in Cellular Neuroscience, 2021)
Abstract: In the central nervous system, myelin is attached to the axon in the paranodal region by a trimolecular complex of Neurofascin155 (NF155) in the myelin membrane, interacting with Caspr1 and Contactin1 on the axolemma. Alternative splicing of a single Neurofascin transcript generates several different neurofascins expressed by several cell types, but NF155, which is expressed by oligodendrocytes, contains a domain in the third fibronectinIII-like region of the molecule that is unique. The immunoglobulin 5-6 domain of NF155 is essential for binding to Contactin1, but less is known about the functions of the NF155-unique third fibronectinIII-like domain. Mutations and autoantibodies to this region are associated with several neurodevelopmental and demyelinating nervous system disorders. Here we used Crispr-Cas9 gene editing to delete a 9 bp sequence of NF155 in this unique domain, which has recently been identified as a thrombin binding site and implicated in plasticity of the myelin sheath. This small deletion results in dysmyelination, eversion of paranodal loops of myelin, substantial enlargement of the nodal gap, a complete loss of paranodal septate junctions, and mislocalization of Caspr1 and nodal sodium channels. The animals exhibit tremor and ataxia, and biochemical and mass spectrometric analysis indicates that while NF155 is transcribed and spliced normally, the NF155 protein is subsequently degraded, resulting in loss of the full length 155 kDa native protein. These findings reveal that this 9 bp region of NF155 in its unique third fibronectinIII-like domain is essential for stability of the protein.